Nigerian Yearbook of International Law 2018/2019 - Eboe-Osuji, Chile; Emeseh, Engobo; Akinkugbe, Olabisi D. (Nigerian Yearbook of International Law, 2021)
The contributions to this volume focus on a diverse array of topics in international law, with scholarly interventions from experts in the field, both in academia and the judiciary, as well as case commentary on a recent decision of the International Court of Justice (Chagos Decision). The theoretical and methodological breadth of the issues covered are relevant to audiences beyond the Nigerian and African intellectual space. In particular, this volume includes analysis on critical intellectual property law questions; intersections of national, regional and international law and technology; the African Continental Free Trade Area Agreement; and maritime law. The authoritative views of the experts on the different issues covered in this volume make excellent contributions to their relevant fields